Risk factors analysis of surgical complications of hepatic hemangioma: a modified Clavien-Dindo classification-based study - Kai Yang; Yan Ma; Zelong Yang; Yanling Yang; Wenjie Song; Weigang Chen; Weihao Lv; Ruohan Zhang; Yong Chen; Hongyu Qiao (BMC Surgery, 2023)
Abstract Purpose There are few studies on the risk factors of postoperative complications after surgical treatment of hepatic hemangioma (HH). This study aims to provide a more scientific reference for clinical treatment. Methods The clinical characteristics and operation data of HH patients undergoing surgical treatment in the First Affiliated Hospital of Air Force Medical University from January 2011 to December 2020 were retrospectively collected. All enrolled patients were divided into two groups based on the modified Clavien-Dindo classification: Major group (Grade II/III/IV/V) and Minor group (Grade I and no complications). Univariate and multivariate regression analysis was used to explore the risk factors for massive intraoperative blood loss (IBL) and postoperative Grade II and above complications. Results A total of 596 patients were enrolled, with a median age of 46.0 years (range, 22–75 years). Patients with Grade II/III/IV/V complications were included in the Major group (n = 119, 20%), and patients with Grade I and no complications were included in the Minor group (n = 477, 80%). The results of multivariate analysis of Grade II/III/IV/V complications showed that operative duration, IBL, and tumor size increased the risk of Grade II/III/IV/V complications. Conversely, serum creatinine (sCRE) decreased the risk. The results of multivariate analysis of IBL showed that tumor size, surgical method, and operative duration increased the risk of IBL. Conclusions Operative duration, IBL, tumor size, and surgical method are independent risk factors that should be paid attention to in HH surgery. In addition, as an independent protective factor for HH surgery, sCRE should attract more attention from scholars.